Loss of Ciliary Gene Bbs8 Results in Physiological Defects in the Retinal Pigment Epithelium - Schneider, Sandra; De Cegli, Rossella; Nagarajan, Jayapriya; Kretschmer, Viola; Matthiessen, Peter Andreas; Intartaglia, Daniela; Hotaling, Nathan; Ueffing, Marius; Boldt, Karsten; Conte, Ivan; May-Simera, Helen Louise (Frontiers in Cell and Developmental Biology, 2021)
Primary cilia are sensory organelles vital for developmental and physiological processes. Their dysfunction causes a range of phenotypes including retinopathies. Although primary cilia have been described in the retinal pigment epithelium (RPE), little is known about their contribution to biological processes within this tissue. Ciliary proteins are increasingly being identified in non-ciliary locations and might carry out additional functions, disruption of which possibly contributes to pathology. The RPE is essential for maintaining photoreceptor cells and visual function. We demonstrate that upon loss of Bbs8, predominantly thought to be a ciliary gene, the RPE shows changes in gene and protein expression initially involving signaling pathways and developmental processes, and at a later time point RPE homeostasis and function. Differentially regulated mole-cules affecting the cytoskeleton and cellular adhesion, led to defective cellular polarization and morphology associated with a possible epithelial-to-mesenchymal transition (EMT)-like pheno-type. Our data highlights the benefit of combinatorial 'omics' approaches with in vivo data for in-vestigating the function of ciliopathy proteins. It also emphasizes the importance of ciliary proteins in the RPE and their contribution to visual disorders, which must be considered when designing treatment strategies for retinal degeneration.